PENENTUAN DAN PENGUKURAN DOSIS SERAP RADIASI SINAR X PADA PERMUKAAN PANTOM KEPALA (SKULL PHANTOM) MENGGUNAKAN METODE ENTRANCE SKIN EXPOSURE (ESE) - Widyanti, Kurnia Nur; Noor, Johan Andoyo; Juswono, Unggul Punjung (Department of Physics - Faculty of Science, 2013)
Entrance skin Exposure (ESE) is a method of determiningÂ surface absorbtion dose in radiation protection. To measure the ESE, we used a the phantom that was made from acrylic and aluminium designed by home made with instruction of American Association of Physicts in Medicine 31 (AAPM 31). This work was aimed to study how far the home phantom comply the AAPM 31 standart. ESE measurements employed x-ray radiaton source of Trophy Omnic Â N60 and radiaton detector of Ionisation chamber type. Measurements of radiation were carried out, they were on primary radiation and exit radiation. The result showsed that ESE value from the measurement was 43,55X10-6 c/kg. There was not much different from the ANSIâs phantom as 54,44x10-6 c/kg. ESEâs value shows an equivalence with value of the theory. Therefore,Â it could be concluded that ordinary acrylic could be used as alternative material for a phantom that be more efisien.